A systematic review of pathways to and processes associated with radicalization and extremism amongst Muslims in Western societies. (February 2015) - McGilloway, Angela; Ghosh, Priyo; Bhui, Kamaldeep
Abstract Following the terrorist attacks of 9/11 in the USA and 7/7 in the UK, academic interest in factors involved in radicalization and terrorism has increased dramatically. Many related social and psychological theories have been put forward, however terrorism literature still lacks empirical research. In particular, little is known about the early processes and pathways to radicalization. Our aim is to investigate original research on pathways and processes associated with radicalization and extremism amongst people of Muslim heritage living in Western societies, that is, the group prioritized by counter-terrorism policy. Studies included in the review were original qualitative or quantitative primary research published in peer-reviewed journals, identified by searching research databases. All disciplines of journals were included. No single cause or pathway was implicated in radicalization and violent extremism. Individuals may demonstrate vulnerabilities that increase exposure to radicalization; however, the only common characteristic determined that terrorists are generally well-integrated, 'normal' individuals. Engagement in such activity is dependent on a wide range of interacting variables influenced by personal, localized and externalized factors. Further research should examine broader determinants of radicalization in susceptible populations. Future policy should follow this public health approach rather than constructing from perpetrators already committed to engaging in terrorism.